An Improved Chloroplast DNA Extraction Procedure for Whole Plastid Genome Sequencing - Shi, Chao (Public Library of Science, 2012)
BACKGROUND: Chloroplast genomes supply valuable genetic information for evolutionary and functional studies in plants. The past five years have witnessed a dramatic increase in the number of completely sequenced chloroplast genomes with the application of second-generation sequencing technology in plastid genome sequencing projects. However, cost-effective high-throughput chloroplast DNA (cpDNA) extraction becomes a major bottleneck restricting the application, as conventional methods are difficult to make a balance between the quality and yield of cpDNAs. METHODOLOGY/PRINCIPAL FINDINGS: We first tested two traditional methods to isolate cpDNA from the three species, Oryza brachyantha, Leersia japonica and Prinsepia utihis. Both of them failed to obtain properly defined cpDNA bands. However, we developed a simple but efficient method based on sucrose gradients and found that the modified protocol worked efficiently to isolate the cpDNA from the same three plant species. We sequenced the isolated DNA samples with Illumina (Solexa) sequencing technology to test cpDNA purity according to aligning sequence reads to the reference chloroplast genomes, showing that the reference genome was properly covered. We show that 40–50% cpDNA purity is achieved with our method. CONCLUSION: Here we provide an improved method used to isolate cpDNA from angiosperms. The Illumina sequencing results suggest that the isolated cpDNA has reached enough yield and sufficient purity to perform subsequent genome assembly. The cpDNA isolation protocol thus will be widely applicable to the plant chloroplast genome sequencing projects.